2021
DOI: 10.1371/journal.pone.0249840
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of prolonged critical illness: A multicentered study in North Brisbane, Australia

Abstract: Background Although critical illness is usually of high acuity and short duration, some patients require prolonged management in intensive care units (ICU) and suffer long-term morbidity and mortality. Objective To describe the long-term survival and examine determinants of death among patients with prolonged ICU admission. Methods A retrospective cohort of adult Queensland residents admitted to ICUs for 14 days or longer in North Brisbane, Australia was assembled. Comorbid illnesses were classified using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…Thus, it is unclear whether frailty affects longer term outcomes after PerCI. It is noteworthy, however, that prior studies have demonstrated particularly poor long-term survival after PerCI (25–50% of initial survivors dead at 1-year), with mortality increasing with age [ 20 , 21 ]. As the prevalence of frailty is considerably greater in older critically ill patients, it is also likely to be an important factor contributing to the disproportionately poor long-term outcomes for older survivors of PerCI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unclear whether frailty affects longer term outcomes after PerCI. It is noteworthy, however, that prior studies have demonstrated particularly poor long-term survival after PerCI (25–50% of initial survivors dead at 1-year), with mortality increasing with age [ 20 , 21 ]. As the prevalence of frailty is considerably greater in older critically ill patients, it is also likely to be an important factor contributing to the disproportionately poor long-term outcomes for older survivors of PerCI.…”
Section: Discussionmentioning
confidence: 99%
“…Articles also had to be of relevance to a prolonged ICU stay, which for this search, included any article listed as an ICU admission for five days or more as this is still considered prolonged when one considers the median LOS being two days (IQR 2-4). 40 We initially sought to include studies with an ICU LOS greater than or equal to seven days to align with the definition of a long-term ICU patient suggested by Alexandersen et al, 41 Dammann et al, 30 and Haugdahl et al 42 but this yielded too few studies for the review. It has been acknowledged in the literature the many definitions used to define a long stay in ICU and the complexity this creates when reviewing the best evidence.…”
Section: Methodsmentioning
confidence: 99%
“…1 Up to 51% of patients with prolonged critical illness may be readmitted to hospital in the first year following discharge 10 and one-year mortality rates are 24.9%. 50 We are, therefore, aware there may be a need to recruit new participants into the study and accept that there may be attrition in the cohort.…”
Section: Limitationsmentioning
confidence: 99%
“…Also, the high morbidity and mortality rate of the study population presents a further limitation. Recent data suggest that in Australia and New Zealand between 18.5% and 24.5% of patients with prolonged critical illness die in hospital 1,50 and only 46.5% are discharged home 1 . Up to 51% of patients with prolonged critical illness may be readmitted to hospital in the first year following discharge 10 and one‐year mortality rates are 24.9% 50 .…”
Section: Limitationsmentioning
confidence: 99%